2013
DOI: 10.1186/2043-7129-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Using metrics and sustainability considerations to evaluate the use of bio-based and non-renewable Brønsted acidic ionic liquids to catalyse Fischer esterification reactions

Abstract: Background: Ionic liquids have found uses in many applications, one of which is the joint solvation and catalysis of chemical transformations. Suitable Brønsted acidic ionic liquids can be formed by combining lactams with sulphonic acids. This work weighs up the relative benefits and disadvantages of applying these Brønsted acidic ionic liquid catalysts in esterifications through a series of comparisons using green chemistry metrics. Results: A new bio-based ionic liquid was synthesised from N-methyl pyrrolidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A fair number of researchers have studied the possibility of substitution of classical acid catalysts with AILs for these reactions. 389 The biodiesel synthesis is in fact a good example of saponification-esterification process; however, biodiesel synthesis is presented as a separate subtopic in this review as it is an extensively studied current application that needs special attention. Therefore, only esterifications and saponifications which are not directly related to biodiesel production are covered in this section.…”
Section: Catalysis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fair number of researchers have studied the possibility of substitution of classical acid catalysts with AILs for these reactions. 389 The biodiesel synthesis is in fact a good example of saponification-esterification process; however, biodiesel synthesis is presented as a separate subtopic in this review as it is an extensively studied current application that needs special attention. Therefore, only esterifications and saponifications which are not directly related to biodiesel production are covered in this section.…”
Section: Catalysis Applicationsmentioning
confidence: 99%
“…Esterification and saponification are industrially important and widely studied acid catalyzed reactions. A fair number of researchers have studied the possibility of substitution of classical acid catalysts with AILs for these reactions . The biodiesel synthesis is in fact a good example of saponification-esterification process; however, biodiesel synthesis is presented as a separate subtopic in this review as it is an extensively studied current application that needs special attention.…”
Section: Applications Of Acidic Ionic Liquidsmentioning
confidence: 99%
“…Recently, the applications of ionic liquids (ILs) in catalysis and especially in the synthesis of biorenewable chemicals have received considerable attention. 55,56 In this regard, Clark et al reported a 50% to 60% yield of EL from LA at 25 °C using an N-methyl-2-pyrrolidonium (NMP) derived IL which has Brønsted acidity, 57 Table 2 (entry 3). However, scaling up processes that use ILs for commercial production remains a challenge.…”
Section: Synthesis Of El From Lamentioning
confidence: 99%
“…From an upscaling perspective, the green metric parameters (such as environmental factor (E-factor), process mass intensity (PMI), atom economy (AE), and carbon efficiency (CE%)) of the glucose interconversion to fructose process were calculated. 48,49 These parameters normally determine a chemical process's feasibility and sustainability. For example, the E-factor signifying the process's environmental impact by accounting for the waste disposal should range between 1 and 5 for a chemical process.…”
Section: Green Matrices Of the Glucose Interconversion Processmentioning
confidence: 99%